Sol-gel synthesis and optical properties of malayaite ceramic colour pigments - N. Yongvanich; N. Wangwanich; N. Phomwana (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ceramic colour pigments based on the malayaite structure was synthesized by sol-gel with an aim to obtain homogeneous powder systems. The formulation was Ca(Sn1-xCrx)SiO5 where x = 0, 0.02 and 0.05. Thermogravimetric analysis and infrared spectroscopy suggested suitable calcination temperatures to be > 1000°C. Formation of malayaite phase was found to be very difficult; high calcination temperatures up to 1400°C was required which was typical for this particular phase. Nevertheless, small amounts of impurities were still present and were found to be both wollastonite (CaSiO3) and cassiterite (SnO2). The oxidation state of chromium was found to be mainly 4+. The obtained pigment particles were in the range of 1-5 micron with a high degree of agglomeration due to sintering. UV-vis spectra demonstrated broad absorbance peak in the 550-600 nm range which could be attributed to both Cr(III) and Cr(IV). The colour parameters in the CIELab system showed a red tone (more positive a* values whereas b* remained relatively constant) when chromium was doped into the malayaite host. Preliminary interaction testing with a low-fire glaze displayed an even improvement in the a* parameter (getting more red tone). Microscopic studies showed a certain degree of chromium diffusion out of the pigment powders toward the glaze matrix. These results have demonstrated a great potential for this refractory colour pigments to be possibly utilized in other kinds of glazes as well.